2019
DOI: 10.2147/dddt.s215358
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cerebral protection of epigallocatechin gallate (EGCG) via preservation of mitochondrial function and ERK inhibition in a rat resuscitation model</p>

Abstract: Background Various and opposite roles of epigallocatechin gallate (EGCG) have been reported in different studies. We aimed to investigate how EGCG affects the cerebral injury in a cardiac arrest/cardiopulmonary resuscitation (CA/CPR) model of rat. Methods The rats which were subjected to CA/CPR randomly received low dose of EGCG (3 mg/kg, Low-EGCG group, n=16), high dose of EGCG (9 mg/kg, High-EGCG group, n=16) and equal volume of 0.9% saline solution (NS group, n=16) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Existing studies report IC 50 of 13 µM for DPPH elimination with EGCG, suggesting that the results of the current study are similar to previous results. 18) It was found that EGCG suppressed ROS production in fibroblasts treated with TNF-α. EGCG has been reported to suppress ROS production in damaged brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies report IC 50 of 13 µM for DPPH elimination with EGCG, suggesting that the results of the current study are similar to previous results. 18) It was found that EGCG suppressed ROS production in fibroblasts treated with TNF-α. EGCG has been reported to suppress ROS production in damaged brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Sprague-Dawley rats were anesthetized and heparinized (0.2 mL, I.P.). Then the CA/CPR rat model was established by the previous method [30] (described in Additional file 1). Rats were randomized into three groups: (1) sham (n = 6), which were subjected to the same procedure as the other groups except for CA/CPR; (2) Control group (n = 6), which underwent 5 min of CA and received injection of same volume of saline; (3) DATS@MION-PEG-LF group (n = 6), which underwent 5 min of CA and received injection of DATS@MION-PEG-LF (10 mg/kg).…”
Section: Rat Ca/cpr Modelmentioning
confidence: 99%
“…Qin et al . [ 43 ], discovered that EGCG played cerebral protective activity after I/R injury via elevating ATP level. In this study, we found that EGCG raised the ATP level in H/R-treated H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%